Science & Language Links : Classroom Implications - Edited by Scott, Johanna (Portsmouth Heinemann, 1993)
This text examines the links that exist between science and language learning and teaching, helping teachers understand how language can support science and how to use science to develop children's language
Include Illustration
Keywords: Science--Study and teaching (Elementary) -- Language arts (Elementary) -- Australia